(untitled) (Interdisciplinary Studies Journal, 2026)
This article analyzes the informational crisis that paralleled the COVID-19 health crisis in Brazil, focusing on how the systematic proliferation of fake news (false, decontextualized, and emotionally appealing stories) acted as a structural force in political and social discourses between 2019 and 2021. The study treats disinformation not as an accidental phenomenon, but as a deliberate strategy to foster scientific denialism, erode public trust, and delegitimize the press, thereby redefining the communication landscape. The methodology is based on a critical literature review on post-truth, surveillance capitalism, and the public sphere (Arendt, Foucault, Habermas, Castells), articulated with an analysis of institutional responses and Brazilian case studies. It concludes that tackling this crisis requires a systemic approach, encompassing platform regulation, strengthening ethical journalism, and investing in media literacy education.